Integration of Google site-based Teaching Materials as Pre Case Based Learning - Asep, Asep (Universitas Lambung Mangkurat, 2024)
Case Based Learning is interpreted as case-based learning in which students are considered to have prior knowledge in solving related cases. As a form of initial knowledge, technology-based teaching materials were developed integrated with Google Site. Through this teaching material, students can use it as initial knowledge before case-based learning is implemented or improved. The development of teaching materials is carried out through the ADDIE model (analysis, Design, Development, Implementation, and Evaluation). Followed by data collection through questionnaires and interviews and analyzed descriptively qualitative. Teaching materials developed with integration into the google site system in the socio-cultural power science course from material expert evaluations with a percentage of 82% and 84% media expert evaluations, this means that the material and media are suitable for use. Furthermore, the feasibility of googel site-based teaching material products from the trial obtained a feasibility percentage of 86%. The use of google site-based teaching materials can be used as an alternative in supporting the effectiveness of case-based learning. This is supported by the accompanying impact in the form of understanding technology-based learning, learning independence, and critical thinking skills.